Curd sensory properties as affected by feeding dairy ewes with cold-pressed oilseed cakes and sainfoin - Pineda-Quiroga C.; García-Rodríguez A.; Goiri I.; Pascual A.; Atxaerandio R.; Ruiz R. (Innovation for sustainability in sheep and goats, 2019)
A lactation study utilizing 72 dairy ewes was performed to determine effects of cold-pressed oilseed cakes, including cold-pressed sunflower cake and cold-pressed rapeseed cake, and their interaction with tanniferous sainfoin hay, on curd sensory properties. A 2 x 3 factorial arrangement involving two forages (tall fescue and sainfoin hay) and 3 experimental concentrates was used. Concentrates were formulated to contain cold-pressed rapeseed cake, cold-preseed sunflower cake or palm as fat sources and to provide equal amounts of crude protein fat and energy. Concentrate type did not affected acceptance traits. Non-significant differences were found between forages in terms of overall acceptability, odour, texture or flavour, but curd appearance was improved when the forage was sainfoin (6.9 vs. 6.4, P=0.011) compared to fescue.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)